Diversitas Burung Di Situ Cihuni - Dita Ayu Kurnia Sari (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2023)
Birds are wild animals that are easy to find in almost every vegetated environment. Its habitat can cover various types of ecosystems, ranging from natural ecosystems to artificial ecosystems, one of which is Situ Cihuni. This research was conducted as an initial step that can be used as a guide for conservation efforts and to determine the balance of aquatic ecosystems. The method used is the field survey method, where the data collected includes the types of birds that are in the transect line and the number of individuals of each bird species found. The results showed that 24 species of birds could be found in Situ Cihuni, with a total encounter of 354 individuals. A diversity index (H') value of 2.23 was obtained, which indicated that the diversity level of bird species in Situ Cihuni was in the moderate category. Then the value of the wealth index (R) is 3.92; the bird with the highest IVI value was the Lonchura punctulata (110.793). Insectivorous bird groups dominate the Situ Cihuni area with a percentage of 46%. The vegetation strata in Situ Cihuni that are most used by birds are strata C and E.